In-Situ Visualization for Cultural Heritage Sites using Novel Augmented Reality Technologies - Didier Stricker; Alain Pagani; Michael Zoellner (Virtual Archaeology Review)
Mobile Augmented Reality is an ideal technology for presenting information in an attractive, comprehensive and personalized way to visitors of cultural heritage sites. One of the pioneer projects in this area was certainly the European project ArcheoGuide (IST-1999-11306) which developed and evaluated Augmented Reality (AR) at a very early stage. Many progresses have been done since then, and novel devices and algorithms offer novel possibilities and functionalities. In this paper we present current research work and discuss different approaches of Mobile AR for cultural heritage. Since this area is very large we focus on the visual aspects of such technologies, namely tracking and computer vision, as well as visualization.